Middle East politics and international relations crisis zone - Akbarzadeh, Shahram; Baxter, Kylie (London Routledge Taylor & Francis Group, 2018)
The Middle East has been defined by political crises for the last 100 years. In the political halls of power, the media, popular culture and the educational institutions of Western countries, the term the 'Middle East' conjures a confused imagery of religion, resources, foreign interference and politics that can be hard to untangle. This book provides a detailed contextualized exploration of the forces, internal and external, that have shaped today's Middle East. Each chapter acts as a stand-alone reading that includes history, context and contemporary implications in a chronological order. Topics explored include: - Imperialism in the Middle East - The formation of the state of Israel - The Arab-Israeli Wars - Palestinian Politics and the failure of the 'peace process' - The Iranian Revolution and pan-Shi'ism - Superpowers in the Middle East - The US-led 'War on Terror' - The Arab Uprisings - The Syrian War and the rise of the 'Islamic State' - US-Iran relations By rethinking the history of the region through the lens of recent developments, this book will be a core reference tool for students of Middle Eastern Politics and International Relations.
Introduction : the colonial background -- The formation of the state of Israel -- The Arab-Israeli wars -- Palestinian politics : the failure of the peace process -- Ideologies and supra state identities -- The Iranian revolution and pan-shi'ism -- Playground for the superpowers -- The US-led "war on terror" -- The Arab uprisings -- The Syrian war and the rise of the "Islamic state" -- Iran coming out of isolation.
Includes bibliographical references (pages 222-231) and index.
Keywords: Middle East -- Politics and government -- 20th century; Middle East -- Politics and government -- 21st century; Middle East -- Foreign relations -- 20th century; Middle East -- Foreign relations -- 21st century